The tadpole of Ameerega boehmei in southeastern Bolivia - French, Connor M.; Burkette, Carmen; Reichle, Steffen; Brown, Jason L. (Zootaxa, 2019)
To date, half (16 of 32) of the species of Ameerega have had their tadpoles described: A. altamazonica, A. bassleri, A. bilinguis, A. braccata, A. cainarachi, A. flavopicta, A. hahneli, A. macero, A. parvula, A. petersi, A. picta, A. rubriventris, A shihuemoy. A. silverstonei, A. smaragdina, and A. trivittata (Lescure, 1976; Silverstone, 1976; Duellman, 1978; Myers & Daly, 1979; Rodriguez & Myers, 1993; Haddad & Martins, 1994; Lötters et al., 1997; Duellman, 2005; Costa et al., 2006; Twomey & Brown, 2008; Brown & Twomey, 2009; Poelman et al., 2010; Schulze et al., 2015). Ameerega boehmei is a putative member of a clade containing Ameerega braccata, A. flavopicta, A. berohoka, A. munduruku, all of which inhabit various parts of the ‘dry diagonal’ between the Amazon and Atlantic rainforests (Prado & Gibbs, 1993). Adult frogs in this group are morphologically similar, generally dark-bodied with yellow dorsolateral stripes, orange flash marks and some also possessing bright-yellow dorsal spots. Despite considerable research on their breeding behavior, acoustics and systematics (Lötters et al., 2009; Forti et al., 2013), the tadpole of Ameerega boehmei, the southern-most and western-most distributed species in this tentative group, has not been described.